Programmable on-chip nonlinear photonics - Ryotatsu Yanagimoto; Benjamin A. Ash; Mandar M. Sohoni; Martin M. Stein; Yiqi Zhao; Federico Presutti; Marc Jankowski; Logan G. Wright; Tatsuhiro Onodera; Peter L. McMahon (Nature, 2026)
Abstract Nonlinear optics 1 plays a central role in many photonic technologies, both classical 2–5 and quantum 6–8 . However, the function of a nonlinear-optical device is typically determined during design and fixed during fabrication 9 , restricting the use of nonlinear optics to scenarios in which this inflexibility is tolerable. Here we present a photonic device with highly programmable nonlinear functionality: an optical slab waveguide with an arbitrarily reconfigurable two-dimensional distribution of χ (2) nonlinearity. The nonlinearity is realized using electric-field-induced χ (2) (refs. 10–16 ), and the programmability is engineered by massively parallel control of the electric-field distribution within the device using a photoconductive layer and optical programming with a spatial light pattern. To showcase the versatility of our device, we demonstrate spectral, spatial and spatio-spectral engineering of second-harmonic generation by tailoring arbitrary quasi-phase-matching grating structures 1 in two dimensions. The programmability of the device makes it possible to perform inverse design of grating structures in situ, as well as real-time feedback to compensate for fluctuations in operating and environmental conditions. Our work shows that we can break from the conventional one-device–one-function paradigm, potentially expanding the applications of nonlinear optics to situations in which fast device reconfigurability is desirable—such as in programmable optical quantum gates and quantum light sources 7,17–19 , all-optical signal processing 20 , optical computation 21 and adaptive structured light for sensing 22–24 .